Impact of Third-party Contract Enforcement in Agricultural Markets—A Field Experiment in Vietnam. (7th May 2014) - Saenger, Christoph; Torero, Maximo; Qaim, Matin
Abstract: We study the effect of alleviating the information asymmetry regarding product quality that is widespread in contracts between agricultural producers and buyers in developing countries. Opportunistic buyers may underreport quality levels to farmers to reduce the price that they have to pay. In response, farmers may curb investment, thereby negatively affecting farm productivity. In an experiment, we entitle randomly selected smallholder dairy farmers in Vietnam, who are contracted by a large company, to independently verify milk testing results. Results indicate that treatment farmers use 12% more inputs, and they also increase their output significantly. Some wider research and policy implications are discussed.